The Fokker-Planck Equation for the System "Brownian Particle in Thermostat" Based on the Presented Probability Approach - Hubal, H.M. (Журнал математической физики, анализа, геометрии, 2010)
A one-dimensional system "Brownian particle in thermostat" is considered. The Fokker-Planck equation describing dynamics of the particle system under consideration is derived on the basis of the presented probability approach. The solution of the derived equation is also obtained.